2020
DOI: 10.33371/ijoc.v14i3.723
|View full text |Cite
|
Sign up to set email alerts
|

Parotid Gland Metastasis From Breast Cancer: A Case Report

Abstract: Introduction: Breast cancer metastasis at the parotid gland is uncommon. There were only 21 cases reported until the recent year, and none of them came from Indonesia. The reports showed that breast cancer metastasis is more often found at the liver, lung, bone, and brain. Therefore, any masses found on the parotid are usually considered as a double primer.Case Presentation: We report a case of a woman, firstly diagnosed with luminal A stage IIA breast cancer at 39 years old. The patient had undergone breast-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%